A comparison of in vivo viral targeting systems identifies adeno‐associated virus serotype 9 (AAV9) as an effective vector for genetic manipulation of Leydig cells in adult mice. (23rd October 2020) - Darbey, Annalucia; Rebourcet, Diane; Curley, Michael; Kilcoyne, Karen; Jeffery, Nathan; Reed, Natalie; Milne, Laura; Roesl, Cornelia; Brown, Pamela; Smith, Lee B.
Abstract: Background: Despite the increasing popularity of deliverable transgenics, a robust and fully validated method for targeting Leydig cells, capable of delivering long‐term transgene expression, is yet to be defined. Objectives: We compared three viral vector systems in terms of their cell targeting specificity, longevity of gene expression and impact on targeted cell types when delivered to the interstitial compartment of the mouse testis. Materials & Methods: We delivered lentiviral, adenoviral and adeno‐associated (AAV) viral particles to the interstitial compartment of adult mouse testis. Immunolocalization and stereology were performed to characterize ability of vectors to target and deliver transgenes to Leydig cells. Results: Viral vectors utilized in this study were found to specifically target Leydig cells when delivered interstitially. Transgene expression in lentiviral‐targeted Leydig cells was detected for 7 days post‐injection before Leydig cells underwent apoptosis. Adenoviral‐delivered transgene expression was detected for 10 days post‐injection with no evidence of targeted cell apoptosis. We found serotype differences in AAV injected testis with AAV serotype 9 targeting a significant proportion of Leydig cells. Targeting efficiency increased to an average of 59.63% (and a maximum of 80%) of Leydig cells with the addition of neuraminidase during injection. In AAV injected testis sections, transgene expression was detectable for up to 50 days post‐injection. Discussion & Conclusion: Lentivirus, Adenovirus and Adeno‐Associated virus delivery to the testis resulted in key variances in targeting efficiency of Leydig cells and in longevity of transgene expression, but identified AAV9 + Neuraminidase as an efficient vector system for transgene delivery and long‐term expression. Simple viral delivery procedures and the commercial availability of viral vectors suggests AAV9 + Neuraminidase will be of significant utility to researchers investigating the genetics underpinning Leydig cell function and holds promise to inform the development of novel therapeutics for the treatment of male reproductive disorders.